2015
DOI: 10.1016/j.ygeno.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome meta-analysis reveals common differential and global gene expression profiles in cystic fibrosis and other respiratory disorders and identifies CFTR regulators

Abstract: A meta-analysis of 13 independent microarray data sets was performed and gene expression profiles from cystic fibrosis (CF), similar disorders (COPD: chronic obstructive pulmonary disease, IPF: idiopathic pulmonary fibrosis, asthma), environmental conditions (smoking, epithelial injury), related cellular processes (epithelial differentiation/regeneration), and non-respiratory "control" conditions (schizophrenia, dieting), were compared. Similarity among differentially expressed (DE) gene lists was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 64 publications
(102 reference statements)
0
31
0
Order By: Relevance
“…23 our own meta-analysis of data of gene expression profile revealed that CF nasal cells' have a significant overlap with genes related to undifferentiated epithelial phenotype 62 .…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…23 our own meta-analysis of data of gene expression profile revealed that CF nasal cells' have a significant overlap with genes related to undifferentiated epithelial phenotype 62 .…”
Section: Accepted Manuscriptmentioning
confidence: 92%
“…Many studies have reported that CFTR functions as a tumour suppressor 14 16 , and some suggested a link between CFTR downregulation in tumour cells and induction of epithelial–mesenchymal transition (EMT) 17 19 . Recent transcriptional profiling analysis revealed impaired epithelial differentiation and an EMT signature in CF airways 20 . However, it is unknown whether EMT is indeed active in CF and if so, what is the trigger, dysfunctional CFTR or a secondary disease event (e.g., chronic inflammation).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analysis documented 873 differentially expressed genes (DEGs) in IPF, and reported significant alternative splicing of 440 genes (Nance et al, ). Comparative transcriptome analyses on IPF, airway epithelial injury and cystic fibrosis demonstrated a strong association of genes in dedifferentiation and epithelial injury, and implied that transcriptional modulations might be commonly observed in the processes including epithelial–mesenchymal transition and inflammation for respiratory fibrogenic diseases (Clarke, Botelho, Sousa, Falcao, & Amaral, ). Nevertheless, the pathogenesis and molecular mechanistic details of IPF may not appropriately represent those of silicosis, and transcriptional evaluations specifically focused on airborne silica toxicity are in demand.…”
Section: Introductionmentioning
confidence: 99%